Effects of Ginsenoside Rg1 Regulating Wnt/β-Catenin Signaling on Neural Stem Cells to Delay Brain Senescence - Yue Xiang; Shun-he Wang; Lu Wang; Zi-ling Wang; Hui Yao; Lin-bo Chen; Ya-ping Wang (Stem Cells International)
This is a study on the relationship between the protective effect of ginsenoside Rg1 on senescent neural stem cells and Wnt-β/catenin signaling pathway. Background. Recent studies have shown that overactivation of the Wnt/β-catenin signaling pathway is closely related to stem cell senescence. Whether Rg1 delays the senescence of NSCs is related to the regulation of this signaling pathway. Methods. The whole brain of Nestin-GFP transgenic newborn rat was extracted, and NSCs were extracted and cultured to P3 generation. The following indicators were detected: (1) NSC culture identification, (2) the effect of LiCl on the proliferation and survival rate of NSCs, (3) the effect of ginsenoside Rg1 on the proliferation and survival of NSCs, (4) the growth of NSCs in each group observed by an optical microscope, (5) the cell cycle of each group detected by flow cytometry, (6) the proliferative ability of each group detected by BrdU, (7) the fluorescence intensity of Nestin and Sox2 of NSCs in each group observed by a fluorescence microscope, (8) the positive rate of senescence staining analyzed by SA-β-Gal staining, (9) the localization of β-catenin in NSCs observed by laser confocal microscopy, and (10) the changes of the Wnt/β-catenin pathway-related proteins in each group detected by Western blotting. Results. LiCl activates the Wnt/β-catenin pathway and promotes mouse neural stem cell senescence. Ginsenoside Rg1 promotes proliferation of neural stem cells and inhibits Wnt/β-catenin pathway activation. Conclusions. LiCl can activate the Wnt/β-catenin signaling pathway of NSCs, and ginsenoside Rg1 can antagonize the senescence of NSCs caused by activation of the Wnt/β-catenin signaling pathway and delay brain aging.